Evolution of HLA-B Pharmacogenomics and the Importance of PGx Data Integration in Health Care System: A 10 Years Retrospective Study in Thailand - Koomdee, Napatrupron; Kloypan, Chiraphat; Jinda, Pimonpan; Rachanakul, Jiratha; Jantararoungtong, Thawinee; Sukprasong, Rattanaporn; Prommas, Santirhat; Nuntharadthanaphong, Nutthan; Puangpetch, Apichaya; Ershadian, Maliheh; John, Shobana; Biswas, Mohitosh; et al. (Frontiers in Pharmacology, 2022)
Background: The HLA-B is the most polymorphicgene, play a crucial role in drug-induced hypersensitivity reactions. There is a lot of evidence associating several risk alleles to life-threatening adverse drug reactions, and a few of them have been approved as valid biomarkers for predicting life-threatening hypersensitivity reactions. Objectives: The objective of this present study is to present the progression of HLA-B pharmacogenomics (PGx) testing in the Thai population during a ten-year period, from 2011 to 2020. Methods: This was a retrospective observational cohort study conducted attheFaculty of Medicine Ramathibodi Hospital. Overall, 13,985 eligible patients who were tested for HLA-B risk alleles between periods of 2011-2020 at the study site were included in this study. Results: The HLAPGx testing has been increasingyear by year tremendously, 94 HLA-B testing was done in 2011; this has been raised to 2880 in 2020. Carbamazepine (n=4069, 33%), allopurinol (n=4675, 38%), and abacavir (n=3246, 26%) were the most common drugs for which the HLA-B genotyping was performed. HLA-B*13:01, HLA-B*15:02 and HLA-B*58:01are highly frequent, HLA-B*51:01 and HLA-B* 57:01are moderately frequent alleles that are being associated with drug induced hypersensitivity. HLA-B*59:01 and HLA-B*38:01 theses alleles are rare but has been reported with drug induced toxicity. Most of the samples were from state hospital (50%), 36% from private clinical laboratories and 14% from private hospitals. Conclusion: According to this study, HLA-BPGx testing is increasing substantially in Thailand year after year. The advancement of research in this field, increased physician awareness of PGx, and government and insurance scheme reimbursement assistance could all be factors. Incorporating PGx data, along with other clinical and non-clinical data, into clinical decision support systems (CDS) and national formularies, on the other hand, would assist prescribers in prioritizing therapy for their patients. This will also aid in the prediction and prevention of serious adverse drug reactions.